Evaluating performance-based financing in low-income and middle-income countries: the need to look beyond average effect - Binyaruka, Peter; Lohmann, Julia; De Allegri, Manuela (BMJ global health, 2020)
### Summary box - - Over the last decade, performance-based financing (PBF) has gained momentum as a health financing innovation, which combines linking healthcare payments to performance with increased provider autonomy and supervision.1 2 The combination of these elements is expected to boost supply-side efforts towards increasing quantity and quality of service provision, triggering a demand-side response towards improved service utilisation.1 3 4 - - A recent paper by Paul et al has critically questioned the widespread introduction of PBF in light of the limited available evidence on its effectiveness.5 The response to this paper has been varied, with authors advancing arguments for and against PBF. Some African PBF implementers have claimed that PBF is an evolving strategy with potential benefits on health systems despite its existing challenges.6 Others have drawn attention to the unintended consequences of PBF7 or to the need to assess the economic value of such an approach.8 Beyond their diverse arguments, however, most authors have concurred with Paul et al 5 on the limited scope of currently available evidence and have postulated the need to better …
Gesehen am 24.09.2020